3D Printed Hybrid Aerogel Gauzes Enable Highly Efficient Hemostasis. Issue 1 (14th October 2022) - Yang, Xiaoxu; Shi, Nan; Liu, Jian; Cheng, Qingqing; Li, Guangyong; Lyu, Jing; Ma, Fengguo; Zhang, Xuetong
Abstract: Hemostatic materials have played a significant role in mitigating traumatic injury by controlling bleeding, however, the fabrication of the desirable material's structure to enhance the accumulation of blood cells and platelets for highly efficient hemostasis is still a great challenge. In this work, directed assembly of poly(vinyl alcohol) (PVA) macromolecules covering the rigid Kevlar nanofiber (KNF) network during 3D printing process is utilized to fabricate hydrophilic, biocompatible, and mechanically stable KNF‐PVA aerogel filaments for effective enriching blood components by fast water absorption. As such, KNF‐PVA aerogel gauzes demonstrate remarkable water permeability (338 mL cm −2 s −1 bar −1 ), water absorption speed (as high as 9.64 g g −1 min −1 ) and capacity (more than ten times of self‐weight), and ability to enrich micron‐sized particles when contacting aqueous solution. All these properties favor efficient hemostasis and the resulting KNF‐PVA aerogel gauzes significantly outperform the commercial product Quikclot Gauze (Z‐Medica) during in vivo experiments with the rat liver laceration model, reducing the hemostasis time by half (60 ± 4 s) and the blood loss by two thirds (0.07 ± 0.01 g). These results demonstrate a robust strategy to design various aerogel gauzes for hemostasis applications. Abstract : Biocompatible and mechanically stable Kevlar nanofiber‐poly(vinyl alcohol) (KNF‐PVA) hybrid aerogel gauzes demonstrating remarkable water permeability, water absorption speed and capacity, and ability to enrich solution‐suspended micronparticles are fabricated via direct‐ink‐writing‐based 3D printing. A prepared aerogel gauzes significantly outperform the commercial product Quikclot Gauze (Z‐Medica) in rat liver laceration injury model, reducing the hemostasis time by half and the blood loss by two thirds.